Use of psychotropic drugs during pregnancy and breast‐feeding. (September 2015) - Larsen, E. R.; Damkier, P.; Pedersen, L. H.; Fenger‐Gron, J.; Mikkelsen, R. L.; Nielsen, R. E.; Linde, V. J.; Knudsen, H. E. D.; Skaarup, L.; Videbech, P.
Abstract : Objective: To write clinical guidelines for the use of psychotropic drugs during pregnancy and breast‐feeding for daily practice in psychiatry, obstetrics and paediatrics. Method: As we wanted a guideline with a high degree of consensus among health professionals treating pregnant women with a psychiatric disease, we asked the Danish Psychiatric Society, the Danish Society of Obstetrics and Gynecology, the Danish Paediatric Society and the Danish Society of Clinical Pharmacology to appoint members for the working group. A comprehensive review of the literature was hereafter conducted. Results: Sertraline and citalopram are first‐line treatment among selective serotonin reuptake inhibitor for depression. It is recommended to use lithium for bipolar disorders if an overall assessment finds an indication for mood‐stabilizing treatment during pregnancy. Lamotrigine can be used. Valproate and carbamazepin are contraindicated. Olanzapine, risperidone, quetiapine and clozapine can be used for bipolar disorders and schizophrenia. Conclusion: It is important that health professionals treating fertile women with a psychiatric disease discuss whether psychotropic drugs are needed during pregnancy and how it has to be administered.